2002
DOI: 10.1001/jama.288.18.2307
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Olfactory Impairment in Older Adults

Abstract: This study demonstrates that prevalence of olfactory impairment among older adults is high and increases with age. Self-report significantly underestimated prevalence rates obtained by olfaction testing. Physicians and caregivers should be particularly alert to the potential for olfactory impairment in the elderly population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

82
948
20
35

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 957 publications
(1,085 citation statements)
references
References 48 publications
82
948
20
35
Order By: Relevance
“…In addition, experimental studies of primate olfaction may prove useful in studies of aging: impairment in odor detection thresholds has been shown to occur in aged persons [18], and in persons with neurodegenerative diseases such as Alzheimer's disease where olfactory impairments have been evidenced in the early stages of the disease [19;20]. As the gray mouse lemur has proved to be a relevant primate model for ageing studies [8], our results open further the possibility to evaluate impairments in cognitive performances in relation to ageing and neurodegenerative diseases in a non human primate model.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, experimental studies of primate olfaction may prove useful in studies of aging: impairment in odor detection thresholds has been shown to occur in aged persons [18], and in persons with neurodegenerative diseases such as Alzheimer's disease where olfactory impairments have been evidenced in the early stages of the disease [19;20]. As the gray mouse lemur has proved to be a relevant primate model for ageing studies [8], our results open further the possibility to evaluate impairments in cognitive performances in relation to ageing and neurodegenerative diseases in a non human primate model.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, performed in different countries, showed that approximately 5 % of the general population is anosmic and about 15 % have reduced olfactory function [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown older adults to be impaired relative to young adults on a variety olfactory tasks (Doty, Shaman, Kimmelman, & Dann, 1984;Gilbert, Pirogovsky, Ferdon, Brushfield, & Murphy, in press;Gilbert, Pirogovsky, Ferdon, & Murphy, 2006;Larsson & Backman, 1998;Murphy, Bacon, Bondi, & Salmon, 1998;Murphy, Cain, Gilmore, & Skinner, 1991;Murphy et al, 2002;Nordin & Murphy, 1998;Wysocki & Gilbert, 1989). Deficits in odor memory have been reported in healthy older adults at risk for AD based on family history (Schiffman, Graham, Sattely-Miller, Zervakis, & Welsh-Bohmer, 2002) or genetic risk factors (Gilbert & Murphy, 2004a, 2004bGraves et al, 1999;Murphy et al, 1998).…”
Section: Introductionmentioning
confidence: 99%